2010
DOI: 10.1243/09544119jeim807
|View full text |Cite
|
Sign up to set email alerts
|

In vitro models for bone mechanobiology: Applications in bone regeneration and tissue engineering

Abstract: Healthy bone healing is a remarkable, mechanically sensitive, scar-free process that leads rapidly to repair tissue of high mechanical quality and functionality, and knowledge of this process is essential for driving advances in bone tissue engineering and regeneration. Gaining this knowledge requires the use of models to probe and understand the detailed mechanisms of healing, and the tight coupling of biology and mechanics make it essential that both of these aspects are controlled and analysed together, usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 63 publications
(61 reference statements)
0
29
0
2
Order By: Relevance
“…This is facilitated through the use of highly porous scaffold architectures, which enable nutrient and metabolite diffusion throughout, while also contributing to the shape and mechanical integrity of the tissue defect. Mechanical stimulation, in the form of fluid perfusion and mechanical compression, have been shown to play an important role in enhancing tissue regeneration and also directing the cellular fate of mesenchymal stem cells (MSCs) (Angele et al 2004;Delaine-Smith and Reilly 2012;Jaasma and O'Brien 2008;Keogh et al 2011;Liu et al 2012b;Miyashita et al 2014; Thompson et al 2010). For example, osteogenic differentiation of MSCs is prompted under mechanical stimulation, as indicated by the increase of Alkaline Phosphatase (ALP), Prostaglandin E 2 (PGE 2 ) expression and mineralisation (Bancroft et al 2002;Grayson et al 2008;Vance et al 2005;Yu et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This is facilitated through the use of highly porous scaffold architectures, which enable nutrient and metabolite diffusion throughout, while also contributing to the shape and mechanical integrity of the tissue defect. Mechanical stimulation, in the form of fluid perfusion and mechanical compression, have been shown to play an important role in enhancing tissue regeneration and also directing the cellular fate of mesenchymal stem cells (MSCs) (Angele et al 2004;Delaine-Smith and Reilly 2012;Jaasma and O'Brien 2008;Keogh et al 2011;Liu et al 2012b;Miyashita et al 2014; Thompson et al 2010). For example, osteogenic differentiation of MSCs is prompted under mechanical stimulation, as indicated by the increase of Alkaline Phosphatase (ALP), Prostaglandin E 2 (PGE 2 ) expression and mineralisation (Bancroft et al 2002;Grayson et al 2008;Vance et al 2005;Yu et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that mechanical stimulation enhances bone tissue regeneration in vitro to a certain extent (Sittichockechaiwut et al 2009;Jaasma et al 2008;Goldstein et al 2001). In particular, it has been shown that osteogenic differentiation, as indicated by ALP, COX 2 and PGE 2 expression (Thompson et al 2010;Keogh et al 2011;Liu et al 2012), is enhanced when bone cells are exposed to the fluid flow, compared to static culture (Jaasma et al 2008;Goldstein et al 2001;Li et al 2009). Such changes could be related to the enhanced nutrient transport or mechanical stimulation of the cells within the scaffolds, but the precise nature of such changes is not yet known.…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41] Under compressive loading 400 to 2,465 μ-strain was recorded at the synthetic bone fracture site with SDCN. This value is consistent with the literature data.…”
Section: Discussionmentioning
confidence: 99%